1981
DOI: 10.1038/ki.1981.63
|View full text |Cite
|
Sign up to set email alerts
|

Selective distal nephron damage during isolated kidney perfusion

Abstract: The morphologic characteristics of the isolated perfused rat kidney were examined by light and electron microscopy. Following perfusion for 90 min, the cortex appeared normal except for the development of spaces in glomerular mesangial regions and ultrastructural abnormalities in very few proximal tubular cells. In the medulla, descending limbs of the loops of Henle and Collecting tubules appeared normal. During perfusion, however, even under optimal conditions, consistent and reproducible changes rapidly deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…In contrast, studies in the isolated kidney have demonstrated that kallikrein is released into the perfusate [9,32], In agree ment with these reports we have found that kallikrein is released into the perfusate of the isolated kidney. We have previously reported [33] that our erythrocyte perfused model is normal morphologically and does not devel op the nephronal injury which occurs in the isolated kidney perfused without red cells [34] , Therefore, our data support the view that kallikrein enters the perfusate by a phys iologic process rather than by the passive loss of the enzyme from injured cells. Release of kallikrein into the perfusate occurs at a con stant rate, equal approximately to 15% of the concurrent rate of urinary excretion.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast, studies in the isolated kidney have demonstrated that kallikrein is released into the perfusate [9,32], In agree ment with these reports we have found that kallikrein is released into the perfusate of the isolated kidney. We have previously reported [33] that our erythrocyte perfused model is normal morphologically and does not devel op the nephronal injury which occurs in the isolated kidney perfused without red cells [34] , Therefore, our data support the view that kallikrein enters the perfusate by a phys iologic process rather than by the passive loss of the enzyme from injured cells. Release of kallikrein into the perfusate occurs at a con stant rate, equal approximately to 15% of the concurrent rate of urinary excretion.…”
Section: Discussionsupporting
confidence: 79%
“…This "no-reflow" phenomenon has also been observed after renal ischaemia due to temporal renal artery occlusion (29). Apart from the existence of this phenomenon, cold ischaemia and reperfusion of the transplant per se could induce cellular energy depletion, particularly of the medullary thick ascending limbs of Henle's loop, äs demonstrated by Alcorn et al (30) in a normothermically perfused isolated kidney preparation. The measurement of the redox state of cytochrome aa 3 in such a preparation gave evidence of near-hypoxic conditions at this site of the nephron (31) due to circulatory conditions (32) and high transport activity (33).…”
Section: Discussionmentioning
confidence: 79%
“…In the absence of erythro cytes, progressive damage to the mTAL occurs while the proximal tubules remain normal [2][3][4], The mTAL damage in this model has been shown to be due to oxygen deprivation resulting from the low oxygen carrying capacity of the cell-free perfusate [3. 4].…”
Section: Discussionmentioning
confidence: 99%
“…In the conventional isolated kidney per fused by a red cell-free medium, the medul lary thick ascending limb (mTAL) undergoes progressive damage during perfusion due to the low oxygen-carrying capacity of the per fusate [2][3][4], We have previously confirmed the finding of Brezis et al [5] that, when the isolated kidney is perfused by an erythrocyteenriched medium, the mTAL remains nor mal [4], Moreover, the isolated erythrocyteperfused kidney (IEPK) has hemodynamic characteristics comparable to those found in vivo, and manifests improved concentrating ability compared to the isolated kidney per fused with a red cell-free medium [6]. Thus the IEPK is a potentially attractive model for the study of renal ishemia.…”
Section: Introductionmentioning
confidence: 99%